The Effectiveness of Health Services Delivered by Community Health Workers on Outcomes Related to Non-Communicable Dis-eases among Elderly People in Rural Areas: A Systematic Review - Vita Widyasari; Ferry Fadzlul Rahman; Kuan-Han Lin; Jiun-Yi Wang (Tehran University of Medical Sciences, 2021)
Background: The number of elderly and the burden of non-communicable diseases increase with time. Community involvement is expected to be an important prevention agent for their neighbors. This study aimed to determine the effectiveness of health services delivered by community health workers (CHWs) which focus on physiological indices related to non-communicable diseases among elderly people and to explain the health services or interventions carried out by CHWs. Methods: This systematic review was conducted based on the PRISMA guidelines. PubMed, ProQuest Science Database, Scopus, EBSCOhost CINAHL, and Web of Science were taken as the source of databases. Manual search was also conducted for articles published before March 2019 without time restriction. The quality of each study was assessed using Critical Checklist by Joanna Briggs Institute. Results: Of the 3,275 initial studies retrieved, 4 studies were included in qualitative synthesis analysis. Three studies arranged a face-to-face interview, while the other study was conducted over the phone. All the 4 studies were intervention studies. Three of them showed a significant improvement in mean systolic blood pressure for the intervention group compared to the control group. The other study showed a significant improvement in weight loss for the intervention group. Conclusion: Health services delivered by CHWs was beneficial to elderly people in rural areas on some physiological indices. It suggested that health services delivered CHWs could contribute toward secondary prevention programs.